Prophylactic Haloperidol Effects on Long-term Quality of Life in Critically Ill Patients at High Risk for Delirium: Results of the REDUCE Study. (August 2019) - Rood, Paul J. T.; Zegers, Marieke; Slooter, Arjen J. C.; Beishuizen, Albert; Simons, Koen S.; van der Voort, Peter H. J.; van der Woude, Meta C. E.; Spronk, Peter E.; van der Hoeven, Johannes G.; Pickkers, Peter; van den Boogaard, Mark
Editor's Perspective: What We Already Know about This Topic: Delirium is a frequently occurring disorder in intensive care unit patients associated with impaired short-term and long-term outcomes Prophylactic haloperidol neither reduces delirium incidence nor its short-term clinical consequences Many intensive care unit survivors suffer from long-term impairment of physical, cognitive, or mental health status, but there is a gap in knowledge regarding which factors are associated with such a change in quality of life in the post–intensive care unit period What This Article Tells Us That Is New: Prophylactic haloperidol does not affect long-term outcome of critically ill patients at high risk for delirium Every additional day of sedation-induced coma is associated with further decline of long-term physical and mental function Background: Delirium incidence in intensive care unit patients is high and associated with impaired long-term outcomes. The use of prophylactic haloperidol did not improve short-term outcome among critically ill adults at high risk of delirium. This study evaluated the effects of prophylactic haloperidol use on long-term quality of life in this group of patients and explored which factors are associated with change in quality of life. Methods: A preplanned secondary analysis of long-term outcomes of the pRophylactic haloperidol usE for DeliriUm in iCu patients at high risk for dElirium (REDUCE) study was conducted. In this multicenter randomized clinical trial, nondelirious intensive care unit patients were assigned to prophylactic haloperidol (1 or 2 mg) or placebo (0.9% sodium chloride). In all groups, patients finally received study medication for median duration of 3 days [interquartile range, 2 to 6] until onset of delirium or until intensive care unit discharge. Long-term outcomes were assessed using the Short Form-12 questionnaire at intensive care unit admission (baseline) and after 1 and 6 months. Quality of life was summarized in the physical component summary and mental component summary scores. Differences between the haloperidol and placebo group and factors associated with changes in quality of life were analyzed. Results: Of 1, 789 study patients, 1, 245 intensive care unit patients were approached, of which 887 (71%) responded. Long-term quality of life did not differ between the haloperidol and placebo group (physical component summary mean score of 39 ± 11 and 39 ± 11, respectively, and P = 0.350; and mental component summary score of 50 ± 10 and 51 ± 10, respectively, and P = 0.678). Age, medical and trauma admission, quality of life score at baseline, risk for delirium (PRE-DELIRIC) score, and the number of sedation-induced coma days were significantly associated with a decline in long-term quality of life. Conclusions: Prophylactic haloperidol use does not affect long-term quality of life in critically ill patients at high risk for delirium. Several factors, including the modifiable factor number of sedation-induced coma days, are associated with decline in long-term outcomes. Abstract : Prophylactic haloperidol does not affect long-term outcome of critically ill patients at high risk for delirium. Every additional day of sedation-induced coma is associated with further decline of long-term physical and mental function.Supplemental Digital Content is available in the text.